An Analysis of the Scientific Attitudes of Fifth Graders through Guided Discovery Learning - Fahrunisa, Amelia; Mustadi, Ali; Toto, Restu Waras; Pudjiastuti, Pratiwi (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study is aimed to investigate the effect of guided discovery learning (GDL) on the fifth graders’ scientific attitudes. A teaching intervention was planned based on GDL which was then practiced in the two science classes (each class with n = 17) at Public Primary School (PPS). The data were collected through questionnaires and were analyzed by comparing the scores of initial and final scientific attitudes of the control and experimental group using independent-samples T-test and the categorization table. The research results show that GDL positively affected the fifth graders’ scientific attitudes. There is a significant difference in the students’ final scientific attitudes scores [t(32)= -3.591;p < 0.05]. This finding implies that GDL is an alternative learning scheme that can be accommodated to foster students’ scientific attitudes. Fostering scientific attitudes builds students’ resilience to cope with today’s and tomorrow’s hoaxes and misconceptions.